Changes in muscle tension of body segments in children with cerebral palsy - Gross N.A. ,; Sharova T.L. ,; Vinokourov L.V. ,; Lebedeva A.L. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify changes in muscle tension in body segments in children with cerebral palsy for an objective analysis of the state of their motor system and the search for effective methods of pedagogical influence on the muscular system in the process of rehabilitation measures. Methods and structure of the study. Children from 6 to 14 years old with a diagnosis of cerebral palsy of varying severity took part in the scientific work. Children were distributed according to the levels of development of gross motor functions on the GMFCS scale. Muscle imbalance, their symmetry, as well as the degree of tension in the muscles of the face, back, back and front of the legs were measured. The studies were carried out using the MES 9000 EMG computer diagnostic system. Results and conclusions. An uneven distribution of muscle tension in the muscle segments of the face and body was revealed, predominantly on the left side (from 34 to 160 mV) in both boys and girls diagnosed with cerebral palsy. Tension of the tibialis muscle of the left leg was noted, which was 135,2 mV and strong tension of the calf muscles of both the left (158,4 mV) and right legs (143,4 mV) with support compensation on the toe of the left leg (60%). Diagnosis of muscle tension and identification of the developmental features of skeletal muscles in children with cerebral palsy is a necessary condition for an objective analysis of the state of their motor system and the search for effective methods of pedagogical influence on the muscular system in the process of rehabilitation measures.